2005
DOI: 10.1111/j.1523-5378.2005.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Colonization with Helicobacter species and the Development of Inflammatory Bowel Disease in Interleukin‐10‐deficient Mice

Abstract: Natural colonization with different Helicobacter species was found in IL-10-/- mice within the same breeding colony. The severity of typhlocolitis differed according to the colonizing Helicobacter species. Furthermore, the rate of typhlocolitis development in IL-10-/- mice naturally colonized with Helicobacter species was significantly slower than that reported in experimentally infected mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
2
28
0
1
Order By: Relevance
“…Lesions in immunocompetent mice consist of mild to moderate lymphoplasmacytic typhlocolitis with occasional lymphoid follicle formation. As lesions progress, mild mucosal hyperplasia also occurs Whary et al 1998), as does intestinal disease in SCID, nude, and RAG1/2 knockout mice (Li et al 1998;Ward et al 1996) and in mice with a variety of targeted mutations of immune system genes, most notably the gene for the immunoregulatory cytokine IL-10 (Burich et al 2001;Erdman et al 2001;Foltz et al 1998;Zhang et al 2005). Intestinal disease in immunocompromised mice can result in rectal prolapse due to severe proliferative typhlocolitis and proctitis.…”
Section: Discoverymentioning
confidence: 95%
See 1 more Smart Citation
“…Lesions in immunocompetent mice consist of mild to moderate lymphoplasmacytic typhlocolitis with occasional lymphoid follicle formation. As lesions progress, mild mucosal hyperplasia also occurs Whary et al 1998), as does intestinal disease in SCID, nude, and RAG1/2 knockout mice (Li et al 1998;Ward et al 1996) and in mice with a variety of targeted mutations of immune system genes, most notably the gene for the immunoregulatory cytokine IL-10 (Burich et al 2001;Erdman et al 2001;Foltz et al 1998;Zhang et al 2005). Intestinal disease in immunocompromised mice can result in rectal prolapse due to severe proliferative typhlocolitis and proctitis.…”
Section: Discoverymentioning
confidence: 95%
“…Most disease studies have focused on H. hepaticus, but several of these other species-including H. bilis Haines et al 1998;Shomer et al 1997), H. rodentium (Maurer et al 2005;Shomer et al 1998;Whary et al 2006), H. trogontum (Moura et al 2003;Whary et al 2006), H. ganmani (Zhang et al 2005), and H. cholecystus -have been associated with a range of lesions that encompass chronic to proliferative typhlocolitis, chronic active hepatitis, and cholangiohepatitis.…”
Section: Discovery Of Other Rodent Helicobacter Speciesmentioning
confidence: 97%
“…Beside the direct pathological effects of EHS, it has been shown that infections of mice by EHS may significantly influence the results of animal experiments (4,5,14,41). However, investigators may not be aware that their laboratory mice are Helicobacter infected because the pathology of EHS is host dependent and infection may be subclinical (39).…”
mentioning
confidence: 99%
“…In susceptible mice, infections with H. typhlonius (12), H. ganmani (41), or H. muridarum (15) are associated with inflammatory bowel disease. Monoinfection with H. rodentium has not been shown to be associated with disease; however, the germ augments inflammatory bowel disease in immunodeficient mice coinfected with H. hepaticus (23).…”
mentioning
confidence: 99%
“…By eliminating IL-10, one would expect to reveal proinflammatory responses generated against enteric pathogens and subsequent pathological manifestations. For instance, C57BL/6 IL-10 Ϫ/Ϫ mice have proved effective in the study of GI tract disease associated with Helicobacter species (15,74). The immunological basis of Helicobacter hepaticus-associated colitis in IL-10 Ϫ/Ϫ mice (33,34), along with bacterial virulence determinants such as cytolethal distending toxin (72), has been studied extensively.…”
mentioning
confidence: 99%